68.1: Invited Paper: Panel Structure Evolution of In‐cell Capacitive Touch Sensor. Issue 1 (June 2015) - Ma, Jun; Yao, Qijun; Lu, Feng; Ma, Conghua; Wang, Lihua; Zhou, Xingyao; Du, Lingxiao; Huang, Zhongshou
Abstract : In this paper, various integration schemes for in‐cell capacitive touch panels will be reviewed. Continuous efforts have been made to eliminate the interference between display and touch sensor structure. A in‐cell LCD module with self‐capacitance touch sensor integrated will be presented.